Risk Factors for Peri-Implantitis: Effect of History of Periodontal Disease and Smoking Habits. A Systematic Review and Meta-Analysis - Claudio Stacchi (eJournal of Oral Maxillofacial Research, 2016)
Objectives: The purpose of this review was to evaluate whether history of periodontitis and smoking habits could represent a risk factor for peri-implantitis and implant loss.